Pengaruh Environmental Leadership dan Environmental Capability Terhadap Firm Performance Dimoderasi dengan Size - Muhammad Rafi; Etty Murwaningsari (Politeknik Ganesha Medan, 2022)
The purpose of the research is to examine the effect of environmental leadership and environmental capabilities on firm performance with moderating variable using the firm size. The financial reports and sustainability reports of companies listed on the IDX in 2020 and 2021 are data utilized in this research. The population used is companies listed on the Indonesia Stock Exchange (IDX) except the financial sector that publishes financial reports and reports from 2020 and 2021. The website of the Indonesian Stock Exchange (IDX) supplied the information for this research. There are 713 companies listed during the research. After removing outlier information, the study's overall sample size is 120 samples that fit the criteria. This study employed the purposive sampling method and the OLS analytic model. In real terms, this research found that environmental leadership has a large and negative impact on firm performance, while environmental capability has a significant and beneficial impact on firm performance. Moderating variable in this research show firm size weakens environmental leadership on firm performance but strengthens environmental capability on firm performance. The control variables in this research show environmental organizational culture, green supply chain management, and green organizational culture have no significant effect on the success of the firm performance.